Effectiveness of Self-compassion Training on Parenting Stress of Mothers with Visually Impaired Children - Zohreh Shams; Zohreh Meshkati; Latifehossadat Madanian (Shiraz University of Medical Sciences, 2021)
Background: This study aims at investigation of the effectiveness of selfcompassiontraining on parenting stress of mothers with visually impairedchildren.Methods: This is a quasi-experimental study with pretest-posttest interventionand a control group. The statistical population of the study included motherswith visually impaired children in Isfahan. Thirty mothers between eighteenand forty years old were selected using purposefully and convenient sampling.Subjects were matched in two groups of 15 intervention and control membersbased on the pre-test score of parenting stress. The intervention group receivedself-compassion training intervention for eight weeks and the control group didnot receive training during this period and was placed on a waiting list. Thequestionnaire used in this study was the parenting stress index. The findingswere analyzed using analysis of covariance by SPSS-23 software.Results: The results showed that self-compassion training significantly reducedparenting stress in the experimental group compared to the control group (P=0.002). Also, in terms of parenting stress in childhood, the mean scores inthe experimental group decreased significantly after intervention compared tothe control group (P=0.018). In terms of parenting stress among parents, themean scores in the experimental group decreased significantly after interventioncompared to the scores in the control group (P=0.0001).Conclusion: Since parenting is associated with stress and parents of visuallyimpaired children suffer more stress, self-compassion training can play animportant role in reducing their parenting stress.